Experience of ensuring the financial capacity of united territorial communities - Kyrylenko, Olga; Baranets, Jaroslav (Herald of Economics, 2020)
Introduction. The ensuring the financial capacity of united territorial communities (UTCs) is crucial for improving the quality and accessibility of services provided to local people, as well as for the development of the local economy, infrastructure and the efficient functioning of united territorial communities in general. However, many united territorial communities are not financially viable, heavily dependent on intergovernmental transfers and lack the necessary resources for economic development. Therefore, to solve these problems it is very important to constantly monitor the financial performance of the formation and use of local budgets of Ukraine, including UTC’s budgets, timely identify existing problems, look for ways to solve them and justify ways to increase UTC’s financial capacity. Methods. The theoretical basis of the study is the scientific developments of domestic and foreign scientists on decentralization, analysis of the problems of ensuring the financial capacity of united territorial communities and finding ways to improve it. The following methods of scientific cognition were used in the research process: induction and deduction, analysis and synthesis, comparison, generalization, analogies and others. The purpose is to evaluate the experience of ensuring the financial capacity of united territorial communities, identify the main problems and develop proposals for increasing the financial capacity of united territorial communities.Conclusions. Based on the analysis and assessment of the level of financial capacity of united territorial communities, the main problems in its provision and growth have been identified. The necessity is substantiated and the directions of increase of financial capacity are outlined. In order to increase the financial capacity of united territorial communities, the proposed ways to increase it are to improve the procedure for paying personal income tax not at the place of registration of taxpayers, but at the location, as well as the use of inter- municipal cooperation between united territorial communities, especially with low financial capacity.Discussion. The prospects for further research are to assess the experience of ensuring the financial capacity of united territorial communities and develop proposals for its improvement.